2003
DOI: 10.1177/105268460301300404
|View full text |Cite
|
Sign up to set email alerts
|

Career Patterns of American Superintendents

Abstract: Stemming from a nationwide survey of superintendents (Glass, Björk, & Brunner, 2000), this article dispels the myth that there is a crisis facing the American school superintendency. Though we note a slight increase in the median age of superintendents, most chief school executives are satisfied in their current positions and tend to stay longer and retire later than they did a decade ago. Further evidence suggests that career patterns and characteristics of women and people of color in the superintendency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…This finding corresponds with our life table and visual displays of hazard. It also falls in line with Björk et al (2003) who found that participants reported first entering the superintendency 1.36 years after certification. Further support for this finding comes from Kowalski et al (2011) who concluded that roughly two thirds of first time superintendents obtained their position within 1 year of beginning their searches.…”
Section: Research Questionsupporting
confidence: 86%
See 4 more Smart Citations
“…This finding corresponds with our life table and visual displays of hazard. It also falls in line with Björk et al (2003) who found that participants reported first entering the superintendency 1.36 years after certification. Further support for this finding comes from Kowalski et al (2011) who concluded that roughly two thirds of first time superintendents obtained their position within 1 year of beginning their searches.…”
Section: Research Questionsupporting
confidence: 86%
“…Figures from descriptive studies support this hypothesis, as the mean superintendent age within most of these studies is in the fifties (Björk, Keedy, & Gurley, 2003;Grissom & Andersen, 2012;Kim & Brunner, 2009). In their national study of U.S. superintendents, Björk et al (2003) found that most entered the position for the first time in their mid-to early forties. Kowalski, McCord, Petersen, Young, and Ellerson (2011) later reported that new superintendents were typically aged between 46 and 50 years.…”
Section: Individual Characteristicsmentioning
confidence: 85%
See 3 more Smart Citations